Influence of PE-CVD and PE-ALD on defect formation in permeation barrier films on PET and correlation to atomic oxygen fluence - Mitschker, F; Steves, S; Gebhard, M; Rudolph, M; Schücke, L; Kirchheim, D; Jaritz, M; Brochhagen, M; Hoppe, Ch; Dahlmann, R; Böke, M; Benedikt, J; et al. (Journal of Physics D: Applied Physics)

Unearthing [3-(Dimethylamino)propyl]aluminium(III) Complexes as Novel Atomic Layer Deposition (ALD) Precursors for Al2O3: Synthesis, Characterization and ALD Process Development - Mai, Lukas; Gebhard, Maximilian; de los Arcos de Pedro, Maria Teresa; Giner, Ignacio; Mitschker, Felix; Winter, Manuela; Parala, Harish; Awakowicz, Peter; Grundmeier, Guido; Devi, Anjana (Chemistry - A European Journal)

Composite targets in HiPIMS plasmas: Correlation of in-vacuum XPS characterization and optical plasma diagnostics - Layes, Vincent; Monje, Sascha; Corbella, Carles; Schulz-von der Gathen, Volker; von Keudell, Achim; de los Arcos de Pedro, Maria Teresa (Journal of Applied Physics)

Nitridische und oxinitridische HPPMS-Beschichtungen für den Einsatz in der Kunststoffverarbeitung (Teil 2) - Bobzin, Kirsten; Grundmeier, Guido; Brögelmann, Tobias; de los Arcos de Pedro, Maria Teresa; Wiesing, Martin; Kruppe, Nathan C. (Vakuum in Forschung und Praxis)

Influence of organic surface chemistry on the nucleation of plasma deposited SiOxfilms - Hoppe, C; Mitschker, F; Giner, I; de los Arcos de Pedro, Maria Teresa; Awakowicz, P; Grundmeier, G (Journal of Physics D: Applied Physics)

Species transport on the target during high power impulse magnetron sputtering - Layes, V.; Monje, S.; Corbella, C.; Trieschmann, J.; de los Arcos de Pedro, Maria Teresa; von Keudell, A. (Applied Physics Letters)

Analysis of the inhibition of thermal degradation of molten polycarbonate at tool steel interfaces by thin TiAlN coatings - Wiesing, M.; de los Arcos de Pedro, Maria Teresa; to Baben, M.; Rueß, H.; Schneider, J.M.; Grundmeier, G. (Polymer Degradation and Stability)

Analysis of dispersive interactions at polymer/TiAlN interfaces by means of dynamic force spectroscopy - Wiesing, M.; de los Arcos de Pedro, Maria Teresa; Gebhard, M.; Devi, A.; Grundmeier, Guido (Physical Chemistry Chemical Physics)
Dispersion forces due to polarizable subsurface layers govern TiAlN/polymer interactions and decrease by 50% when oxidizing TiAlN to form TiAlO.

Adhesion of plasma-deposited silicon oxide barrier layers on PDMS containing polypropylene - Hoppe, C.; Mitschker, F.; Awakowicz, P.; Kirchheim, D.; Dahlmann, R.; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Surface and Coatings Technology)

The enzyme-mediated autodeposition of casein: effect of enzyme immobilization on deposition of protein structures - Ruediger, Arne A.; Bremser, Wolfgang; Strube, Oliver I. (Journal of Coatings Technology and Research)

Nanoscaled Biocoatings via Enzyme Mediated Autodeposition of Casein - Ruediger, Arne A.; Bremser, Wolfgang; Strube, Oliver I. (Macromolecular Materials and Engineering)

Influences on the film thickness in the enzymatic autodeposition process of casein - Ruediger, Arne A.; Terborg, Elke; Bremser, Wolfgang; Strube, Oliver I. (Progress in Organic Coatings)

Enzyme-Mediated In Situ Synthesis and Deposition of Nonaggregated Melanin Protoparticles - Strube, Oliver I.; Büngeler, Anne; Bremser, Wolfgang (Macromolecular Materials and Engineering)

Influence of the Surface and Heat Treatment on the Bond Strength of Galvanized Steel/Aluminum Composites Joined by Plastic Deformation - Hoppe, Christian; Ebbert, Christoph; Grothe, Richard; Schmidt, Hans Christian; Hordych, Illia; Homberg, Werner; Maier, Hans Juergen; Grundmeier, Guido (ADVANCED ENGINEERING MATERIALS)
The influence of a chemical or mechanical surface modification followed by different post-heat treatments on the bond strength of galvanized steel/ aluminum composites is studied. An incremental rolling process is used for joint formation based on plastic deformation. The morphology, the chemical state of the modified surfaces as well as the cross-section, and local potential distribution of the welded zone is characterized by different microscopic and spectroscopic methods. The stability of the joint is analyzed by a shear-force test in combination with microscopic failure analysis. A clear correlation between pre/post-treatment and the joint strength is observed.

Molecular Engineering of Aluminum-Copper Interfaces for Joining by Plastic Deformation - Hoppe, Christian; Ebbert, Christoph; Voigt, Markus; Schmidt, Hans Christian; Rodman, Dmytro; Homberg, Werner; Maier, Hans Juergen; Grundmeier, Guido (ADVANCED ENGINEERING MATERIALS)
Interface modification based on ultra-thin mercapto-propyl(trimethoxy) silane (MPTMS) films is shown to promote joining of copper and aluminum by plastic deformation followed by a heat treatment. The surface morphology and the surface chemistry of the metal substrates were analyzed by means of FE-SEM, XPS, and FT-IRRAS. The spectroscopic data show that the MPTMS film is crosslinked via Si-O-Si bonds and that stable Cu-S and Si-O-Al interfacial bonds are formed. The shear-force tests of the joints led to force displacement curves that are characteristic for a covalently bonded interface. Complementary cross sectional SEM and EDS analysis of the joint proved that a defect-free interface was formed without any measureable interdiffusion of metals across the interface or cracking of an oxide films.

Nanoscale Structure of the Oil-Water Interface - Fukuto, M.; Ocko, B. M.; Bonthuis, D. J.; Netz, R. R.; Steinrück, Hans-Georg; Pontoni, D.; Kuzmenko, I.; Haddad, J.; Deutsch, M. (Physical Review Letters)

In Situ Study of Silicon Electrode Lithiation with X-ray Reflectivity - Cao, Chuntian; Steinrück, Hans-Georg; Shyam, Badri; Stone, Kevin H.; Toney, Michael F. (Nano Letters)

Self-Assembly, Dynamics, and Polymorphism of hIAPP(20–29) Aggregates at Solid–Liquid Interfaces - Hajiraissi, Roozbeh; Giner, Ignacio; Grundmeier, Guido; Keller, Adrian (Langmuir)

Regular Nanoscale Protein Patterns via Directed Adsorption through Self-Assembled DNA Origami Masks - Ramakrishnan, Saminathan; Subramaniam, Sivaraman; Stewart, A. Francis; Grundmeier, Guido; Keller, Adrian (ACS Applied Materials & Interfaces)

Temperature-Dependent Charge Transport through Individually Contacted DNA Origami-Based Au Nanowires. - Teschome, B; Facsko, S; Schönherr, T; Kerbusch, J; Keller, Adrian; Erbe, A (Langmuir)

DNA annealing by Redβ is insufficient for homologous recombination and the additional requirements involve intra- and inter-molecular interactions. - Subramaniam, S; Erler, A; Fu, J; Kranz, A; Tang, J; Gopalswamy, M; Ramakrishnan, S; Keller, Adrian; Grundmeier, Guido; Müller, D; Sattler, M; Stewart, AF (Scientific Reports)

Plasma-Enhanced Chemical Vapor Deposition (PE-CVD) yields better Hydrolytical Stability of Biocompatible SiOx Thin Films on Implant Alumina Ceramics compared to Rapid Thermal Evaporation Physical Vapor Deposition (PVD) - Böke, Frederik; Giner, Ignacio; Keller, Adrian; Grundmeier, Guido; Fischer, Horst (ACS Applied Materials & Interfaces)

Anisotropic metal growth on phospholipid nanodiscs via lipid bilayer expansion - Oertel, Jana; Keller, Adrian; Prinz, Julia; Schreiber, Benjamin; Hübner, René; Kerbusch, Jochen; Bald, Ilko; Fahmy, Karim (Scientific Reports)

Structural stability of DNA origami nanostructures in the presence of chaotropic agents - Ramakrishnan, Saminathan; Krainer, Georg; Grundmeier, Guido; Schlierf, Michael; Keller, Adrian (Nanoscale)

Adsorption and adhesion studies of PdSn-nanoparticles on protonated amine and carboxylic acid-terminated surfaces - Mosebach, Bastian; Bayer, Frank Markus; Fels, Carl-Christian; Voigt, Markus; Oezkaya, Berkem; Pomorska, Agata; Torun, Boray; Keller, Adrian; Grundmeier, Guido (Surface and Interface Analysis)

The Thermal Oxidation of TiAlN High Power Pulsed Magnetron Sputtering Hard Coatings as Revealed by Combined Ion and Electron Spectroscopy - Wiesing, Martin; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Advanced Materials Interfaces)

Electric potential screening on metal targets submitted to reactive sputtering - Corbella, Carles; Marcak, Adrian; von Keudell, Achim; de los Arcos de Pedro, Maria Teresa (Journal of Vacuum Science & Technology A: Vacuum, Surfaces, and Films)

Nitridische und oxinitridische HPPMS-Beschichtungen für den Einsatz in der Kunststoffverarbeitung (Teil 1) - Bobzin, Kirsten; Grundmeier, Guido; Brögelmann, Tobias; de los Arcos de Pedro, Maria Teresa; Wiesing, Martin; Kruppe, Nathan C. (Vakuum in Forschung und Praxis)

(Cr,Al)N/(Cr,Al)ON Oxy-nitride Coatings deposited by Hybrid dcMS/HPPMS for Plastics Processing Applications - Bobzin, K.; Brögelmann, T.; Grundmeier, G.; de los Arcos de Pedro, Maria Teresa; Wiesing, M.; Kruppe, N.C. (Surface and Coatings Technology)

Influence of O2 exposure on the interaction between CH4 and amorphous AlYB14 - Hunold, Oliver; Wiesing, Martin; de los Arcos de Pedro, Maria Teresa; Music, Denis; Grundmeier, Guido; Schneider, Jochen M. (Applied Surface Science)

Revising secondary electron yields of ion-sputtered metal oxides - Corbella, Carles; Marcak, Adrian; de los Arcos de Pedro, Maria Teresa; von Keudell, Achim (Journal of Physics D: Applied Physics)

An efficient PE-ALD process for TiO2 thin films employing a new Ti-precursor - Gebhard, M.; Mitschker, F.; Wiesing, M.; Giner, I.; Torun, B.; de los Arcos de Pedro, Maria Teresa; Awakowicz, P.; Grundmeier, G.; Devi, A. (Journal of Materials Chemistry C)
A new Ti-precursor for low-temperature PE-ALD of titanium dioxide thin films as gas barrier layers on polymer substrates.

Combined Electrochemical and Electron Spectroscopic Investigations of the Surface Oxidation of TiAlN HPPMS Hard Coatings - Wiesing, Martin; to Baben, Moritz; Schneider, Jochen M.; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Electrochimica Acta)

Buildup of biobased adhesive layers by enzymatically controlled deposition on the example of casein - Strube, Oliver I.; Rüdiger, Arne A.; Bremser, Wolfgang (International Journal of Adhesion and Adhesives)

Site-Specific In Situ Synthesis of Eumelanin Nanoparticles by an Enzymatic Autodeposition-Like Process - Strube, Oliver I.; Büngeler, Anne; Bremser, Wolfgang (Biomacromolecules)

Structure of n-Alkyltrichlorosilane Monolayers on Si(100)/SiO2 - Steinrück, Hans-Georg; Will, J.; Magerl, A.; Ocko, B. M. (Langmuir)

Order and Melting in Self-Assembled Alkanol Monolayers on Amorphous SiO2 - Haddad, Julia; Steinrück, Hans-Georg; Hlaing, Htay; Kewalramani, Sumit; Pontoni, Diego; Reichert, Harald; Murphy, Bridget M.; Festersen, Sven; Runge, Benjamin; Magnussen, Olaf M.; Magerl, Andreas; Deutsch, Moshe; et al. (The Journal of Physical Chemistry C)

Structural Investigations of Self-Assembled Monolayers for Organic Electronics: Results from X-ray Reflectivity - Khassanov, Artoem; Steinrück, Hans-Georg; Schmaltz, Thomas; Magerl, Andreas; Halik, Marcus (Accounts of Chemical Research)

In situ investigation of two-step nucleation and growth of CdS nanoparticles from solution - Schiener, A.; Magerl, A.; Krach, A.; Seifert, S.; Steinrück, Hans-Georg; Zagorac, J.; Zahn, D.; Weihrich, R. (Nanoscale)

Alignment of Gold Nanoparticle-Decorated DNA Origami Nanotubes: Substrate Prepatterning versus Molecular Combing - Teschome, Bezu; Facsko, Stefan; Gothelf, Kurt V.; Keller, Adrian (Langmuir)

Fundamental understanding of the corrosion and biomineralization of MgO surfaces – An in situ AFM study - Giner, Ignacio; Keller, Adrian; Grundmeier, Guido (Corrosion Science)

Low-aspect ratio nanopatterns on bioinert alumina influence the response and morphology of osteoblast-like cells - Wittenbrink, Isabel; Hausmann, Anne; Schickle, Karolina; Lauria, Ines; Davtalab, Roswitha; Foss, Morten; Keller, Adrian; Fischer, Horst (Biomaterials)

On the way to identify microorganisms in drinking water distribution networks via DNA analysis of the gut content of freshwater isopods - Mayer, Michael; Keller, Adrian; Szewzyk, Ulrich; Warnecke, Hans-Joachim (Journal of Biotechnology)

Fundamentals and Applications of Reflection FTIR Spectroscopy for the Analysis of Plasma Processes at Materials Interfaces - Grundmeier, Guido; von Keudell, Achim; de los Arcos de Pedro, Maria Teresa (Plasma Processes and Polymers)

Spectroscopic and Microscopic Investigations of Degradation Processes in Polymer Surface-Near Regions During the Deposition of SiOx Films - Mitschker, Felix; Dietrich, Jan; Ozkaya, Berkem; de los Arcos de Pedro, Maria Teresa; Giner, Ignacio; Awakowicz, Peter; Grundmeier, Guido (Plasma Processes and Polymers)

Characteristics of a propagating, self-pulsing, constricted ‘γ-mode-like’ discharge - Schröder, Daniel; Burhenn, Sebastian; de los Arcos de Pedro, Maria Teresa; Schulz-von der Gathen, Volker (Journal of Physics D: Applied Physics)

Note: Ion-induced secondary electron emission from oxidized metal surfaces measured in a particle beam reactor - Marcak, Adrian; Corbella, Carles; de los Arcos de Pedro, Maria Teresa; von Keudell, Achim (Review of Scientific Instruments)

Processing of New Materials by Additive Manufacturing: Iron-Based Alloys Containing Silver for Biomedical Applications - Niendorf, Thomas; Brenne, Florian; Hoyer, Kay-Peter; Schwarze, Dieter; Schaper, Mirko; Grothe, Richard; Wiesener, Markus; Grundmeier, Guido; Maier, Hans Jürgen (Metallurgical and Materials Transactions A)

Joining with electrochemical support (ECUF): Cold pressure welding of copper - Ebbert, Christoph; Schmidt, H. C.; Rodman, D.; Nuernberger, F.; Homberg, W.; Maier, H. J.; Grundmeier, Guido (JOURNAL OF MATERIALS PROCESSING TECHNOLOGY)
Joining metals using electrochemical support (ECUF) is a new process for cold pressure welding sheets and parts. This new process is based on an electrochemical in-line surface treatment followed by incremental pilger rolling. The ECUF process intends to cold pressure weld materials under optimized conditions. Oxide layers on metal surfaces are known to inhibit the formation of cold pressure welds. The in-line electrochemical treatment will be used to remove these surface oxides for specific engineering metals and alloys. Hence, an improved pressure weld formation at lower forces and smaller reduction ratios is expected for the electrochemically treated surfaces. Using a more flexible pressure welding process, the number of applications could be greatly improved. First tests with copper were performed to analyse the efficiency of the proposed electrochemical surface treatments. Two electrochemical treatments, the cathodic oxide-reduction and cyclovoltammetric oxide-reduction, were compared with conventional treatments (degreasing and scratch brushing) regarding their influence on the cold pressure welding process of copper. The weld strength of lap welds has been investigated as well as the necessary reduction threshold to form a weld. It was found that the electrochemical oxide reduction resulted in higher weld strength. The results of scanning electron microscopy (SEM) and energy dispersive analysis of X-rays (EDX) indicate that surface oxides were successfully removed by the electrochemical surface treatments. (C) 2014 Elsevier B.V. All rights reserved.

Nanoscale Structure of Si/SiO2/Organics Interfaces - Steinrück, Hans-Georg; Schiener, Andreas; Schindler, Torben; Will, Johannes; Magerl, Andreas; Konovalov, Oleg; Li Destri, Giovanni; Seeck, Oliver H.; Mezger, Markus; Haddad, Julia; Deutsch, Moshe; Checco, Antonio; et al. (ACS Nano)

Interface Engineering of Molecular Charge Storage Dielectric Layers for Organic Thin-Film Memory Transistors - Khassanov, Artoem; Schmaltz, Thomas; Steinrück, Hans-Georg; Magerl, Andreas; Hirsch, Andreas; Halik, Marcus (Advanced Materials Interfaces)

Tuning the molecular order of C60-based self-assembled monolayers in field-effect transistors - Schmaltz, Thomas; Khassanov, Artoem; Steinrück, Hans-Georg; Magerl, Andreas; Hirsch, Andreas; Halik, Marcus (Nanoscale)

Pseudorotational Epitaxy of Self-Assembled Octadecyltrichlorosilane Monolayers on Sapphire (0001) - Steinrück, Hans-Georg; Magerl, A.; Deutsch, M.; Ocko, B. M. (Physical Review Letters)

Molecular Processes Studied at a Single-Molecule Level Using DNA Origami Nanostructures and Atomic Force Microscopy - Bald, Ilko; Keller, Adrian (Molecules)

X-Ray Photoelectron Spectroscopy Investigations of the Surface Reaction Layer and its Effects on the Transformation Properties of Nanoscale Ti51Ni38Cu11Shape Memory Thin Films - König, Dennis; Naujoks, Dennis; de los Arcos de Pedro, Maria Teresa; Grosse-Kreul, Simon; Ludwig, Alfred (Advanced Engineering Materials)

Description of HiPIMS plasma regimes in terms of composition, spoke formation and deposition rate - de los Arcos de Pedro, Maria Teresa; Schröder, Raphael; Gonzalvo, Yolanda Aranda; Gathen, Volker Schulz-von der; Winter, Jörg (Plasma Sources Science and Technology)

Carbon nanotube growth on AlN support: Comparison between Ni and Fe chemical states and morphology - Eren, Baran; Marot, Laurent; Steiner, Roland; de los Arcos de Pedro, Maria Teresa; Düggelin, Marcel; Mathys, Daniel; Goldie, Kenneth N.; Olivieri, Vesna; Meyer, Ernst (Chemical Physics Letters)

Simultaneous characterization of static and induced magnetic fields in high power impulse magnetron sputtering discharges - Machura, P D; Hecimovic, A; Gallian, S; Winter, J; de los Arcos de Pedro, Maria Teresa (Plasma Sources Science and Technology)

Adsorption and reactivity of nitrogen atoms on silica surface under plasma exposure - Marinov, D; Guaitella, O; de los Arcos de Pedro, Maria Teresa; von Keudell, A; Rousseau, A (Journal of Physics D: Applied Physics)

Nanostructured Er2O3 Thin Films Grown by Metalorganic Chemical Vapour Deposition - Xu, Ke; Dang, Van-Son; Ney, Andreas; de los Arcos de Pedro, Maria Teresa; Devi, Anjana (Journal of Nanoscience and Nanotechnology)

Plasma-polymerized HMDSO coatings to adjust the silver ion release properties of Ag/polymer nanocomposites - Alissawi, N.; Peter, T.; Strunskus, T.; Ebbert, Christoph; Grundmeier, Guido; Faupel, F. (JOURNAL OF NANOPARTICLE RESEARCH)
In the current work, we study the silver ion release potential and the water uptake through a SiOxCyHz-polymer which is grown from the precursor hexamethyldisiloxane (HMDSO) in radiofrequency (RF) plasma. These layers were deposited on top of two dimensional (2D) ensembles of silver nanoparticles (AgNPs) with nominal thickness of 2 nm on a 20 nm RF-sputtered polytetrafluoroethylene (PTFE) thin film. The composition of the plasma-polymerized HMDSO barriers was varied by changing the oxygen flow during the polymerization process and their thickness was varied as well. Morphology and optical properties of the nanocomposites were investigated using transmission electron microscopy (TEM) and UV-Visible spectroscopy (UV-Vis), respectively. The concentration of the silver ions released from the nanocomposites after immersion in water for several time intervals was measured using inductively coupled plasma mass spectrometry (ICP-MS). Contact angle analysis and electrochemical impedance spectroscopy (EIS) measurements were also performed and results show a strong dependence of the coatings properties and their water uptake on the oxygen content in the coating films and their thickness. Plasma polymerization with increasing the oxygen flow leads to the formation of more hydrophilic thin films with a higher Ag ion release potential. Increasing the thickness of the coatings reduced the amount of the released ions and the rate of the release process was slowed down. This indicates that by tailoring the structure and the thickness of the plasma-polymerized coating films, one can tune the silver ion release properties of Ag/polymer nanocomposites.

Region-Selective Self-Assembly of Functionalized Carbon Allotropes from Solution - Wang, Zhenxing; Mohammadzadeh, Saeideh; Schmaltz, Thomas; Kirschner, Johannes; Khassanov, Artoem; Eigler, Siegfried; Mundloch, Udo; Backes, Claudia; Steinrück, Hans-Georg; Magerl, Andreas; Hauke, Frank; Hirsch, Andreas; et al. (ACS Nano)

Low-Voltage Self-Assembled Monolayer Field-Effect Transistors on Flexible Substrates - Schmaltz, Thomas; Amin, Atefeh Y.; Khassanov, Artoem; Meyer-Friedrichsen, Timo; Steinrück, Hans-Georg; Magerl, Andreas; Segura, Juan José; Voitchovsky, Kislon; Stellacci, Francesco; Halik, Marcus (Advanced Materials)

Oxygen diffusivity in silicon derived from dynamical X-ray diffraction - Will, J.; Gröschel, A.; Kot, D.; Schubert, M. A.; Bergmann, C.; Steinrück, Hans-Georg; Kissinger, G.; Magerl, A. (Journal of Applied Physics)

Electrical and optical properties of TiO2thin films prepared by plasma-enhanced atomic layer deposition - Dang, Van-Son; Parala, Harish; Kim, Jin Hyun; Xu, Ke; Srinivasan, Nagendra B.; Edengeiser, Eugen; Havenith, Martina; Wieck, Andreas D.; de los Arcos de Pedro, Maria Teresa; Fischer, Roland. A.; Devi, Anjana (physica status solidi (a))

MOCVD of tungsten nitride thin films: Comparison of precursor performance and film characteristics - Srinivasan, Nagendra B.; Thiede, Tobias B.; de los Arcos de Pedro, Maria Teresa; Rogalla, Detlef; Becker, Hans-Werner; Devi, Anjana; Fischer, Roland A. (physica status solidi (a))

Atomic layer deposition of Er2O3 thin films from Er tris-guanidinate and water: process optimization, film analysis and electrical properties - Xu, Ke; Chaudhuri, Ayan Roy; Parala, Harish; Schwendt, Dominik; de los Arcos de Pedro, Maria Teresa; Osten, H. Jörg; Devi, Anjana (Journal of Materials Chemistry C)

Transition metal nitride thin films grown by MOCVD using amidinato based complexes [M(NtBu)2{(iPrN)2CMe}2] (M=Mo, W) as precursors - Srinivasan, N.B.; Thiede, T.B.; de los Arcos de Pedro, Maria Teresa; Gwildies, V.; Krasnopolski, M.; Becker, H.-W.; Rogalla, D.; Devi, A.; Fischer, R.A. (Surface and Coatings Technology)

Target implantation and redeposition processes during high-power impulse magnetron sputtering of aluminum - Will, Andreas; de los Arcos de Pedro, Maria Teresa; Corbella, Carles; Hecimovic, Ante; Machura, Patrick D; Winter, Jörg; von Keudell, Achim (Journal of Physics D: Applied Physics)

Particle beam experiments for the analysis of reactive sputtering processes in metals and polymer surfaces - Corbella, Carles; Grosse-Kreul, Simon; Kreiter, Oliver; de los Arcos de Pedro, Maria Teresa; Benedikt, Jan; von Keudell, Achim (Review of Scientific Instruments)

Instabilities in high-power impulse magnetron plasmas: from stochasticity to periodicity - Winter, J; Hecimovic, A; de los Arcos de Pedro, Maria Teresa; Böke, M; Schulz-von der Gathen, V (Journal of Physics D: Applied Physics)

Insight into the Reaction Scheme of SiO2 Film Deposition at Atmospheric Pressure - Rügner, Katja; Reuter, Rüdiger; Ellerweg, Dirk; de los Arcos de Pedro, Maria Teresa; von Keudell, Achim; Benedikt, Jan (Plasma Processes and Polymers)

pH-dependent structure and energetics of H2O/MgO(100) - Thissen, Peter; Thissen, Vera; Wippermann, Stefan; Chabal, Yves J.; Grundmeier, Guido; Schmidt, Wolf Gero (Surface Science)

Fabrication of ZrO2 and ZrN Films by Metalorganic Chemical Vapor Deposition Employing New Zr Precursors - Banerjee, Manish; Srinivasan, Nagendra Babu; Zhu, Huaizhi; Kim, Sun Ja; Xu, Ke; Winter, Manuela; Becker, Hans-Werner; Rogalla, Detlef; de los Arcos de Pedro, Maria Teresa; Bekermann, Daniela; Barreca, Davide; Fischer, Roland A.; et al. (Crystal Growth & Design)

Sc2O3, Er2O3, and Y2O3 thin films by MOCVD from volatile guanidinate class of rare-earth precursors - Milanov, Andrian P.; Xu, Ke; Cwik, Stefan; Parala, Harish; de los Arcos de Pedro, Maria Teresa; Becker, Hans-Werner; Rogalla, Detlef; Cross, Richard; Paul, Shashi; Devi, Anjana (Dalton Transactions)

The Role of Oxygen and Surface Reactions in the Deposition of Silicon Oxide like Films from HMDSO at Atmospheric Pressure - Reuter, Rüdiger; Rügner, Katja; Ellerweg, Dirk; de los Arcos de Pedro, Maria Teresa; von Keudell, Achim; Benedikt, Jan (Plasma Processes and Polymers)

High power impulse magnetron sputtering discharges: Instabilities and plasma self-organization - Ehiasarian, A. P.; Hecimovic, A.; de los Arcos de Pedro, Maria Teresa; New, R.; Schulz-von der Gathen, V.; Böke, M.; Winter, J. (Applied Physics Letters)

Nanocomposites of carbon nanotubes embedded in a (Ti,Al)N coated film - Marot, L.; de los Arcos de Pedro, Maria Teresa; Bünzli, A.M.; Wäckerlin, C.; Steiner, R.; Oelhafen, P.; Meyer, E.; Mathys, D.; Spätig, P.; Covarel, G. (Surface and Coatings Technology)

Embedded argon as a tool for sampling local structure in thin plasma deposited aluminum oxide films - Prenzel, Marina; de los Arcos de Pedro, Maria Teresa; Kortmann, Annika; Winter, Jörg; von Keudell, Achim (Journal of Applied Physics)

Temporal evolution of the radial plasma emissivity profile in HIPIMS plasma discharges - Hecimovic, A; de los Arcos de Pedro, Maria Teresa; Schulz-von der Gathen, V; Böke, M; Winter, J (Plasma Sources Science and Technology)

Influence of target surfaces on the atomic oxygen distribution in the effluent of a micro-scaled atmospheric pressure plasma jet - Schröder, D; Bahre, H; Knake, N; Winter, J; de los Arcos de Pedro, Maria Teresa; Schulz-von der Gathen, V (Plasma Sources Science and Technology)

PM-IRRAS studies of the adsorption and stability of organophosphonate monolayers on passivated NiTi surfaces - Maxisch, M.; Ebbert, Christoph; Torun, B.; Fink, N.; de los Arcos, T.; Lackmann, J.; Maier, H. J.; Grundmeier, Guido (APPLIED SURFACE SCIENCE)
Alkylphosphonic acids of different alkyl chain lengths were adsorbed on electrochemically polished NiTi surfaces from ethanolic solutions. The electropolishing process led to passive films mainly composed of Ti-oxyhydroxide. The surface showed nanoscopic etching pits with a depths of about 2 nm and a diameter of about 20 nm. The interfacial binding mechanism of the phosphonic acid group to the oxyhydroxide surface and the ordering of the monolayer were spectroscopically analysed by means of infrared reflection absorption FTIR-spectroscopy with (PM-IRRAS) and without (IRRAS) photoelastic modulation. The comparison of IRRAS and PM-IRRAS data of the long chain octadecylphosphonic acid monolayer proved that the binding mechanism of the phosphonic acid group to the oxyhydroxide surface is based on a mono-or bidentate bond, which is not stable in the presence of high water activities. An alkyl chain length of 17 CH2 groups is required for the formation of self-assembled monolayers, which are stable in aqueous environments. These long chain aliphatic organophosphonic acid monolayers were shown to inhibit anodic and cathodic surface reactions. (C) 2010 Elsevier B.V. All rights reserved.

Liquid-Phase Epitaxy of Multicomponent Layer-Based Porous Coordination Polymer Thin Films of [M(L)(P)0.5] Type: Importance of Deposition Sequence on the Oriented Growth - Zacher, Denise; Yusenko, Kirill; Bétard, Angèlique; Henke, Sebastian; Molon, Mariusz; Ladnorg, Tatjana; Shekhah, Osama; Schüpbach, Björn; de los Arcos de Pedro, Maria Teresa; Krasnopolski, Michael; Meilikhov, Mikhail; Winter, Jörg; et al. (Chemistry - A European Journal)

Influence of process parameters on the crystallinity, morphology and composition of tungsten oxide-based thin films grown by metalorganic chemical vapor deposition - de los Arcos de Pedro, Maria Teresa; Cwik, Stefan; Milanov, Andrian P.; Gwildies, Vanessa; Parala, Harish; Wagner, Tristan; Birkner, Alexander; Rogalla, Detlef; Becker, Hans-Werner; Winter, Jörg; Ludwig, Alfred; Fischer, Roland A.; et al. (Thin Solid Films)

Evaluation of Homoleptic Guanidinate and Amidinate Complexes of Gadolinium and Dysprosium for MOCVD of Rare-Earth Nitride Thin Films - Thiede, Tobias B.; Krasnopolski, Michael; Milanov, Andrian P.; de los Arcos de Pedro, Maria Teresa; Ney, Andreas; Becker, Hans-Werner; Rogalla, Detlef; Winter, Jörg; Devi, Anjana; Fischer, Roland A. (Chemistry of Materials)

X-ray photoelectron spectroscopy on implanted argon as a tool to follow local structural changes in thin films - Lahrood, Atena Rastgoo; de los Arcos de Pedro, Maria Teresa; Prenzel, Marina; von Keudell, Achim; Winter, Jörg (Thin Solid Films)

Dissociative and molecular adsorption of water onα-Al2O3(0001) - Wippermann, S.; Schmidt, Wolf Gero; Thissen, P.; Grundmeier, G. (physica status solidi (c))

PM-IRRAS studies of the adsorption and stability of organophosphonate monolayers on passivated NiTi surfaces - Maxisch, M.; Ebbert, C.; Torun, B.; Fink, N.; de los Arcos de Pedro, Maria Teresa; Lackmann, J.; Maier, H.J.; Grundmeier, G. (Applied Surface Science)

Dissociative and molecular adsorption of water onα-Al2O3(0001) - Wippermann, S.; Schmidt, Wolf Gero; Thissen, P.; Grundmeier, Guido (physica status solidi (c))

Water adsorption on the α-Al2O3(0001) surface - Thissen, P.; Grundmeier, G.; Wippermann, S.; Schmidt, Wolf Gero (Physical Review B)

Water adsorption on hydrogenated Si(111) surfaces - Lange, B.; Posner, R.; Pohl, K.; Thierfelder, C.; Grundmeier, Guido; Blankenburg, S.; Schmidt, Wolf Gero (Surface Science)

The importance of catalyst oxidation for the growth of carbon nanotubes on Si substrates - de los Arcos de Pedro, Maria Teresa; Oelhafen, Peter; Mathys, Daniel (Carbon)

On the graphitisation role of oxide supports in carbon nanotube CVD synthesis - Rümmeli, M. H.; Schäffel, F.; de los Arcos de Pedro, Maria Teresa; Haberer, D.; Bachmatiuk, A.; Kramberger, C.; Ayala, P.; Borowiak-Palen, E.; Adebimpe, D.; Gemming, T.; Leonhardt, A.; Rellinghaus, B.; et al. (physica status solidi (b))

The Influence of Catalyst's Oxidation Degree on Carbon Nanotube Growth as a Substrate-Independent Parameter - de los Arcos de Pedro, Maria Teresa; Oelhafen, Peter; Thommen, Verena; Mathys, Daniel (The Journal of Physical Chemistry C)

Optical characterization of alignment and effective refractive index in carbon nanotube films - de los Arcos de Pedro, Maria Teresa; Oelhafen, P; Mathys, D (Nanotechnology)

Organometallic Block Copolymers as Catalyst Precursors for Templated Carbon Nanotube Growth - Hinderling, C.; Keles, Y.; Stöckli, T.; Knapp, H. F.; de los Arcos de Pedro, Maria Teresa; Oelhafen, P.; Korczagin, I.; Hempenius, M. A.; Vancso, G. J.; Pugin, R.; Heinzelmann, H. (Advanced Materials)

The Influence of Catalyst Chemical State and Morphology on Carbon Nanotube Growth - de los Arcos de Pedro, Maria Teresa; Garnier, Michael Gunnar; Seo, Jin Won; Oelhafen, Peter; Thommen, Verena; Mathys, Daniel (The Journal of Physical Chemistry B)

Strong influence of buffer layer type on carbon nanotube characteristics - de los Arcos de Pedro, Maria Teresa; Gunnar Garnier, M; Oelhafen, Peter; Mathys, Daniel; Won Seo, Jin; Domingo, Concepción; Vicente Garcı́a-Ramos, José; Sánchez-Cortés, Santiago (Carbon)

Photoemission study of the iron-induced chemical reduction of silicon native oxide - Garnier, M.G.; de los Arcos de Pedro, Maria Teresa; Boudaden, J.; Oelhafen, P. (Surface Science)

Is aluminum a suitable buffer layer for carbon nanotube growth? - de los Arcos de Pedro, Maria Teresa; Wu, Z.M.; Oelhafen, P. (Chemical Physics Letters)